PEMBUATAN BAHAN BAKAR DARI PIROLISIS LIMBAH PLASTIK JENIS POLIETILEN, POLISTIREN DAN OTHER - Gunawan Budi Susilo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
Pyrolysis processis definedas a reaction to chemical degradation caused by heat energy with little/absence of oxygen. Pyrolysis of waste plastics into liquid fuels using a batch reactor in which the heatingis set at a temperature of 450oC. This study was conducted to determine the properties of mixed plastic waste pyrolysis oil PE 50% + PS 50%, PE 50% + Other 50% , PE 50% +PS 25% + Other 25% include specific gravity, kinematic viscosity, pour point, flash point,water content and ash content. The results of the calculation of the percentage ofthe highest pyrolysis oil is a mixture of PE 50% + PS 50% of 52.36%, while the lowest percentage is a mixture of PE 50% + Other 50% at 43.41%. Polystyrene plastic addition type increase in the percentage of liquid, the higher the percentage, the percentage of liquid plastic Polystyrene produce higher. Conversely with the addition of plastic Other resulted in a decrease in the percentage of liquid product. Characteristics of pyrolysis fuel oil for specific gravity, and water content is higher than biodiesel. Conversely to kinematic viscosity, flash point, and lower ash content. Pour point to a mixture PE 50% + PS 25% + Other 25 % equivalent to biodiesel (60C), PE 50% and 50% PS (-120C) is lower than biodiesel and PE 50% +Other 50% (120C) higher of biodiesel.